Ni(OH)2 nanowires/graphite foam composite as an advanced supercapacitor electrode with improved cycle performance. (27th July 2016) - Chen, Yang; Zhang, Zilan; Sui, Zhijun; Liu, Zhiting; Zhou, Jinghong; Zhou, Xinggui
Abstract: The demand for supercapacitors with high energy density has been increasing to meet the requirements of recycle energy systems. In this work, a composite material consists of Ni(OH)2 nanowires and graphite foam was prepared by a facile and low cost hydrothermal method. The structure and morphology of the composite were characterized by N2 physisorption, X-ray diffraction, thermogravimetric analysis, scanning electron microscopy and Raman spectroscopy. The capacitive properties of the samples were tested by cyclic voltammetry, galvanostatic charge–discharge and electrochemical impedance spectrum. The results showed that the Ni(OH)2 of nanowires were incorporated into the three dimensional porous carbon framework to form a Ni(OH)2 nanowires/graphite foam composite with high surface area and interconnected mesoporosity. The electrode based on the as-obtained composite exhibits specific capacitance up to 2144 F g −1 in 6 mol L −1 KOH electrolyte at 1A g −1 owing to the high capacitive Ni(OH)2 nanowires and its unique nanostructure, which provided the easy diffusion of electrolyte into the inner region of the electrode. Furthermore, an asymmetric supercapacitor using Ni(OH)2 nanowires/graphite foam as positive electrode and activated carbon as negative electrode was fabricated and exhibited high cell voltage of 1.8 V, energy density of 59 Wh kg −1 and superior long cycle life with 97% specific capacitance retained after 3000 cycles. The excellent cycling stability is related to the close combination of Ni(OH)2 nanowires and graphite foam, enhancing the resilience to the deforming of composite nanostructure during the charge/discharge process. The results demonstrated that NW/GF composite is a promising candidate as an electrode material for supercapacitors. Graphical abstract: A 3-dimensional composite material consists of Ni(OH)2 nanowires and graphite foam was prepared by a facile and low cost hydrothermal method, exhibiting excellent specific capacitance and good cycling stability. Highlights: NW/GF was prepared by a facile and low cost hydrothermal method. NW/GF has unique 3D nanostructure with high surface area and interconnected mesoporosity. An asymmetric supercapacitor based on NW/GF as positive electrode was fabricated. NW/GF electrode material exhibited superior specific capacitance and excellent cycling stability.